Single-center experience of Ex vivo liver resection and autotransplantation for complex hepatic alveolar echinoccosis - Yuan, Jiaqi; Chen, Xiaobin; Hou, Lizhao; Wang, Haijiu; Zhou, Ying; Pang, Mingquan; YangDan, CaiRang; Wang, Zhixin; Fan, Haining (Frontiers in Surgery, 2023)
Objective To summarize the single-centre experience of Ex vivo Liver Resection and Autotransplantation (ELRA) to treat end-stage hepatic alveolar echinococcosis (HAE). Methods Retrospective analysis of clinical data and follow-up data of 13 patients admitted to the Affiliated Hospital of Qinghai University from January 2015 to December 1, 2020, with the Ex vivo Liver Resection and Autotransplantation for hepatic alveolar echinococcosis. Result 13 patients underwent successful total/ semi-ex-vivo liver resection combined with Ex vivo Liver Resection and Autotransplantation with no intra-operative deaths. the median standard liver volume was 1,118 ml (1,085–1,206.5 ml); the median residual liver volume was 634 ml (526.5–1,338 ml); The median weight of the autograft was 845.8 g (619.5–1,020.5 g), the median operation time was 14.5 h (11.5–16.15 h); the median anhepatic period time was 290 min (257–312.5 min). The median intraoperative blood loss was 1,900 ml (1,300–3,500 ml); the median number of erythrocyte suspensions entered was 7.5 u (6–9u). The median length of hospital stay was 32 days (24–40 days). Postoperative complications occurred in 9 patients during hospitalization,with 7 patients graded at grade III or higher by Clavien-Dindo; 4 patients died postoperatively. 1 patient had recurrent abdominal distension with massive thoracoabdominal fluid and coagulation dysfunction 8 months after surgery and was considered to have small liver syndrome. 1 patient developed HAE recurrence during the follow-up, which was considered intraoperative incisional implantation. Conclusion ELRA is one of the most valuable therapeutic measures for the treatment of end-stage complicated hepatic alveolar echinococcosis. Precise preoperative assessment of liver function, individualized intraoperative duct reconstruction, and precise management of the postoperative disease can achieve better treatment results.